Methotrexate-Associated Lymphoproliferative Disorder With Gingival Swelling - Saki Manabe; Masayuki Oki; Ayaki Sano; Takuto Nishimura; Ryohei Tomita; Shota Sato; Toru Ishihara; Hidetaka Yanagi; Hideki Ozawa (Annals of Internal Medicine: Clinical Cases)
A 63-year-old Japanese man being treated for pemphigus vulgaris with methotrexate (MTX) presented with a fever of unknown origin. His only symptom at onset was mild gingival swelling. Suspected to have gingivitis, he was followed for 1 month. After that, he presented with cervical lymphadenopathy, dysphagia, and bicytopenia, and a diagnosis of MTX-associated lymphoproliferative disorder (MTX-LPD) was finally made by gingival biopsy. He had spontaneous remission after the withdrawal of MTX. When MTX-treated patients complain of fever and oral lesions, even if the oral lesions present as mild gingival swellings, physicians should consider MTX-LPD and perform a diagnostic biopsy.